RELASI FILSAFAT DAN SINEMA: SEBUAH PROYEKSI ATAS PEMIKIRAN GILLES DELEUZE DALAM CINEMA 1, CINEMA 2 DAN WHAT IS PHILOSOPHY? - , SULUH P. W, Rr. Siti Murtiningsih, S.S., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The background of this study was the lack of philosophical practice in responding the existence and the development of cinema as a new entity. Cinema emerged in the end of 19th century and started to develop along the 20th century until today century. Recognizing that unproductive phenomena, Gilles Deleuze considered Henri Bergson as an exception. It was because shortly after the Lumiere brothers represented cinematograph, Bergson came up with the discourse about the importance of the new way of thinking in understanding movement. Bergson composed a concept about movement-image and time-image